Carbimazole-induced agranulocytosis treated with propylthiouracil - Das, Shemee; Chowdhury, Chirantan; Kar, Antara; Kashem, Chowdhury Tanvir Ibne; Uddin, Md Rafiq; Mallick, Satyajit; Akter, Farhana (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Antithyroid drugs may result in serious adverse events which require prompt alteration of therapy and adequate supportive measures. A 29-year-old female patient presented with a history of swelling in front of her neck for 3 months and cough, sore throat, and palpitation for 1 month. She was diagnosed as a case of Hyperthyroidism and was prescribed carbimazole 15 mg thrice daily. She was relatively well for 2 weeks with medications but after that, she experienced high-grade fever with chills and rigors associated with sore throat. Then she consulted with an Endocrinologist and was started on granulocyte colony-stimulating factor (G-CSF) with discontinuation of carbimazole. Barrier nursing and a broad-spectrum antibiotic (3rd generation cephalosporins) were used to treat her neutropenic sepsis and propylthiouracil was initiated. Her symptoms resolve following radio-iodine ablation and her thyroid function status is currently euthyroid. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 35-37